World of science : sen copy masters - Coppock, David; Coppock, Carol (New York : Oxford university press, 2000)
With 160 photocopiable sheets, this title aims to encourage and motivate less able students. It includes a set of writing frames to help with literacy across the curriculum as stressed in the 2000 National Curriculum. It also adds a fourth level of differentiation to World of Science to build a differentiated scheme of work.
Keywords: Science -- Study and teaching (Secondary).; Science -- Problems, exercises, etc